ANALISIS YURIDIS PENEGAKAN HUKUM PIDANA TERHADAP PENYEBARAN BERITA HOAX COVID-19 MELALUI MEDIA SOSIAL - Bella Alberta Jeslin Eka Putri (Universitas Muhammadiyah Metro, 2021)
In the dissemination of news and information, not all of them can be justified or what is usually referred to as a hoax. Hoax is information that is engineered with the aim of covering up real information and filling social media with wrong information to cover up real information, in other words, hoaxes are defined as a way to distort facts by using information that is convincing but cannot be done. One of the hoaxes that is currently always a public concern in Indonesia is hoax news about Covid-19. A lot of information about covid-19 that is disseminated through social media can be accepted by almost all people and this information cannot be justified or is in uncertainty. it can cause panic and psychological pressure or can even lead to misunderstanding between communities and governments. For those who spread hoax news about Covid-19, it is also difficult to overcome. Criminal law enforcement related to the spread of covid-19 hoax news is regulated in Law 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. The perpetrators of spreading hoaxes related to covid19 and others with fines of up to 1 billion. This is what the government needs to pay attention to in an effort to deal with all hoax news that has circulated widely in the community.